2021
DOI: 10.1111/jog.15060
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vaginal and endometrial microbiota by real‐time PCR in women with unexplained infertility

Abstract: AimMicrobiota of the reproductive tract may be associated with unexplained infertility in women. We aimed to determine the derangements of vaginal and endometrial microbiota related to unexplained infertility by real‐time polymerase chain reaction (real‐time PCR) microbiota analyses of vaginal and endometrial samples of the unexplained infertility patients and fertile women.Materials and MethodsTwenty‐six women with unexplained infertility and 26 age‐matched fertile women were included. Vaginal and endometrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…No statistically significant differences were observed between corresponding fresh and frozen samples, allowing the conclusion that samples can be frozen prior to processing. Previous studies reported samples for vaginal microbiome analysis have been processed immediately after collection [ 14 ], but this obviously causes challenges in the research and clinical setting. The ability to freeze samples before processing allows flexibility in sample collection, batch processing and thus, will result in cost savings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No statistically significant differences were observed between corresponding fresh and frozen samples, allowing the conclusion that samples can be frozen prior to processing. Previous studies reported samples for vaginal microbiome analysis have been processed immediately after collection [ 14 ], but this obviously causes challenges in the research and clinical setting. The ability to freeze samples before processing allows flexibility in sample collection, batch processing and thus, will result in cost savings.…”
Section: Discussionmentioning
confidence: 99%
“…The development of new technology has enabled rapid analysis of the vaginal microbiome with ease using quantitative real-time polymerase chain reaction (qPCR) [ 14 ]. The vaginal microbiome is not routinely assessed but in certain research settings and private scenarios, women can access the test, which is usually undertaken through a vaginal swab [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…(Babu et al ., 2017), Ureaplasma spp . ( Wee et al ., 2018 ), Chlamydia trachomatis ( Graspeuntner et al ., 2018 ), Mycoplasma hominis ( Sezer et al ., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…A study found that infertile women show characteristic variations in vaginal microbiome, such as the increased abundance of Atopobium, Aerococcus, and Bifidobacterium and decreased abundance of Lactobacillus and Leuconostoc (Zhao et al, 2020). In the unexplained infertility patients, the colonization rate of Lactobacillus in vaginal samples was lower, and the mean proportion of Lactobacillus/total bacterial was significant reduction (Sezer et al, 2022).…”
Section: Discussionmentioning
confidence: 99%